'The Brazilian Rhône': Economic Development of the Doce River Basin in Nineteenth-Century Brazil, 1819–49'. Issue 1 (12th October 2015) - BIEBER, JUDY
Abstract: This article examines attempts to modernise navigation of the Doce River in Brazil during the early nineteenth century. It focuses primarily on the development of a joint Anglo-Brazilian business venture, The Rio Doce Company (1832–49). The failure of the Rio Doce Company cannot be attributed to a single overarching cause, but reflects numerous barriers to economic development including a cumbersome regulatory bureaucracy, capital scarcity, poor technological integration, challenging topography, and Brazilian political resistance to British investment and corporate oversight. This article contributes to the field of business history in the immediate post-independence era, a topic that has received relatively little scholarly attention. Spanish abstract: Este artículo examina los intentos por modernizar la navegación del Río Doce en Brasil a comienzos del siglo XIX. Se centra principalmente en el desarrollo de una empresa anglo-brasileña, la Compañía del Río Doce (1832–49). El fracaso de dicha compañía no se puede atribuir a una sola causa fundamental, sino que refleja numerosas barreras al desarrollo económico tales como una enredada burocracia regulatoria, escasez de capital, pobre integración económica, una topografía difícil y la resistencia política a la inversión británica y su control corporativo. Este artículo contribuye al campo de la historia comercial en la era inmediata de la post-independencia, un tema que ha recibido relativamente poca atención académica. Portuguese abstract: Este artigo examina as tentativas de modernizar a navegação do Rio Doce no Brasil, durante o início do século XIX. Foca-se majoritariamente no desenvolvimento de uma joint venture anglo-brasileira: a Companhia Rio Doce (1832–49). O fracasso da Companhia Rio Doce não pode ser atribuído a uma única causa abrangente, mas a diversas barreiras ao desenvolvimento econômico, incluindo uma burocracia regulatória demasiadamente complicada, escassez de capital, integração tecnológica insuficiente, topografia complexa, e a uma resistência política brasileira a investimentos britânicos e supervisão corporativa. Este artigo contribui para o campo da história empresarial no período logo após a independência, tópico que tem recebido relativamente pouca atenção acadêmica.